WAA apheresis registry in the Czech Republic: two centers experience - Bláha, Milan; Pták, Jan; Čáp, Jan; Ceeová, Věra; Mašín, Vladimír; Filip, Stanislav; Blažek, Martin (Transfusion and apheresis science, 2009)
INTRODUCTION: Hemaphereses are sophisticated procedures performed for many indications even in severely ill patients. Many authors consider quite necessary to register as many details as possible of treatments with therapeutic apheresis. WAA meets the requirement to compare data with centers not performing apheresis for the same diagnosis. In Czech Republic hemaphereses are used in a broad spectrum of indications. Since the year 2004 data on hemaphereses done in Czech Republic have been registered. In this paper we present a survey of our to date recordings. PATIENTS AND METHODS: Data of performed therapeutic hemaphereses (plasma exchange, erythrocytapheresis, leukapheresis, thrombocytapheresis, photopheresis, immunopheresis, and rheopheresis) have been entered in WAA registry with many details. We have been evaluated 1289 procedures in 216 patients done in our two centers (center I, center II). RESULTS: Center I registered 129 procedures in 41 patients, center II 1260 procedures in 175 patients. The patients are divided according to centers specialization (center II has registered 12 long-term treated patients with LDL-apheresis; mean time of therapy 7.1 years and a median of 34 procedures/patient. Side-effects registered in center I and center II were 3.1% and 5.6% of the procedures, respectively. Most frequent side-effects were citrate toxicity, neurovegetative lability, problems with venous access and hypotension. All were easy to treat, no serious events or death occurred. CONCLUSIONS: In Czech Republic hemaphereses are performed in a broad scale of indications and now it is nearly 5 years that data are registered in our two university centers. In 2004 we entered WAA registry because it meets the requirement to compare data with centers that do not perform aphereses for the same diagnosis. This comparison would certainly improve efficacy of the hemapheresis therapy even further. To enter WAA registry is easy, at no expense and without any problems.
Keywords: Young Adult; Male; mladý dospělý; hypercholesterolemie; Hypercholesterolemia; separace krevních složek; Česká republika; Plateletpheresis; Plasma Exchange; fotoferéza; Adult; Plasmapheresis; dospělí; mužské pohlaví; registrace; Leukocyte Transfusion; transfuze erytrocytů; výměna plazmy; Photopheresis; Czech Republic; lidé; transfuze leukocytů; plazmaferéza; ženské pohlaví; Platelet Transfusion; Humans; transfuze trombocytů; trombocytaferéza; Registries; Female; Erythrocyte Transfusion; lidé středního věku; Blood Component Removal; Middle Aged